Hierarchical structures emerge from the cultural transmission: an iterated learning experiment using a non-linguistic task - Nakata, Seiya; Takezawa, Masanori (Frontiers in Artificial Intelligence, 2023)
Human language is characterized by complex structural features, such as the hierarchical combination of words to form sentences. Although other animals use communication systems, empirical evidence of hierarchical structures is rare. Computational studies of language evolution have suggested that cultural transmission plays a key role in the emergence of structural features in human languages, including hierarchy. While Cornish et al. (2013) demonstrated the emergence of hierarchical structures in non-linguistic systems, we argue that their laboratory study may have overestimated the role of cultural transmission because of a lack of appropriate controls and analyses. To directly test the effect of cultural transmission, we conducted an experiment with no cultural transmission as a control (individual condition) in addition to replicating Cornish et al.'s (2013) transmission experiment (transmission condition). Our study has added a quantitative analysis of the hierarchical depth. We found that sequences became more structured as the number of generations increased; however, those produced under the transmission condition were more structured than those under the individual condition. These findings suggest that cultural transmission plays an important role in the emergence of hierarchical structures, which cannot be explained by increased learnability alone. The emergence of complex structural properties in human culture, such as language, technology, and music, may have resulted from information transmission processes between different individuals. In conclusion, this study provides evidence of the crucial role of cultural transmission in the emergence of hierarchical structures in non-linguistic communication systems. Our results contribute to the ongoing debate on the origins of human language and the emergence of complex cultural artifacts. The results of this study have implications for the study of cultural evolution and the role of transmission in shaping the emergence of structural features across diverse domains.